1989
DOI: 10.1042/bj2570679
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between human blood-coagulation factor VIII and von Willebrand factor. Characterization of a high-affinity binding site on factor VIII

Abstract: The interaction between human Factor VIII and immobilized multimeric von Willebrand Factor (vWF) was characterized. Equilibrium binding studies indicated the presence of multiple classes of Factor VIII-binding sites on vWF. The high-affinity binding (Kd = 2.1 x 10(-10) M) was restricted to only 1-2% of the vWF subunits. Competition studies with monoclonal antibodies with known epitopes demonstrated that the Factor VIII sequence Lys1673-Arg1689 is involved in the high-affinity interaction with vWF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
85
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(93 citation statements)
references
References 29 publications
6
85
0
2
Order By: Relevance
“…This Initial studies supported that vWF interacts with the acidic amino acid-rich amino terminus of the FVIII light chain. mAbs to residues 1670-1689 inhibit interaction with vWF (46)(47)(48) and deletion of a portion of this region destroys high-affinity vWF interaction (47). However, the isolated acidic peptide 1648-1689 was incapable of binding vWF, suggesting the vWF interaction requires other regions of the FVIII molecule.…”
Section: Discussionmentioning
confidence: 99%
“…This Initial studies supported that vWF interacts with the acidic amino acid-rich amino terminus of the FVIII light chain. mAbs to residues 1670-1689 inhibit interaction with vWF (46)(47)(48) and deletion of a portion of this region destroys high-affinity vWF interaction (47). However, the isolated acidic peptide 1648-1689 was incapable of binding vWF, suggesting the vWF interaction requires other regions of the FVIII molecule.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of FVIII to vWF is important for the survival of FVIII as the plasma concentration of FVIII is considerably reduced in the absence of vWF (6)(7)(8). FVIII binds to vWF involving A3 and C2 domains of the light chain (9)(10)(11)(12)(13). It has been shown that the A2, A3, and C2 domains of FVIII are involved in the interaction with LRP (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Upon proteolytic activation, FVIIIa is released from VWF as a heterotrimer composed of the A1 and A2 domains plus the FVIIIa light chain, A3-C1-C2. Activated platelet membranes expose negatively charged phosphatidylserine (PS), which increases from 2% to 10% or more of the surface phospholipids upon activation.…”
Section: Introductionmentioning
confidence: 99%